Crystal change ink, preparation method thereof and ceramic rock plate
By developing a crystallized ink containing a crystallized glaze and an inorganic active agent, the problems of harmful substances in the application of existing ceramic functional inks are solved, and high glossiness is achieved. Even and delicate glaze effect and performance improvement.
Patent Information
- Application Number
- CN202411551746.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The existing ceramic functional inks have problems such as the use of harmful substances, high production costs, prone to defects and performance limitations in their applications.
A variable crystal ink was developed, whose raw material components include variable crystal glaze, inorganic active agent and ink additives, and a stable crystal structure was formed by high temperature firing, resulting in unique texture and color changes.
It has achieved the reduction of the use of harmful substances, reduced production costs, improved gloss and transparency, enhanced the visual effect and adhesion of the product, and the glaze surface is uniform and delicate, without obvious defects.
Smart Images

Figure CN119432162A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic inks, and in particular relates to a metamorphic ink and a preparation method thereof, and a ceramic rock plate. Background Art
[0002] Ceramic inkjet technology has become an important symbol of technological innovation in the architectural ceramics industry. Products decorated with this technology show increasingly rich patterns and colors and a strong sense of three-dimensionality, and can realistically simulate a variety of natural textures such as oil paintings, wood grain, and stone. With the widespread application and advancement of ceramic inkjet technology, inkjet printing equipment, especially inkjet flower machines, has also experienced rapid development, continuously promoting technological progress in equipment, inks, and product innovation in this field. Ceramic ink manufacturers continue to innovate, from basic color inks to inks with specific functions, greatly expanding the diversity and innovation of ceramic products.
[0003] In the wide application of ceramic inkjet technology, glossy ink and matte ink, as important components of ceramic functional ink, each show their unique decorative charm. Glossy ink is sprayed onto the surface of ceramic tiles through the print nozzle of the ceramic inkjet machine, creating a bright and smooth effect and a decorative texture with high reflectivity, giving the product a bright visual experience and delicate glaze texture, achieving rich and accurate color gradients, making the pattern vivid and delicate, and showing artistic charm. In contrast, matte ink provides a dull and low-reflectivity texture, adding a low-key and elegant decorative effect, enhancing the visual impact and three-dimensional texture of the product, and meeting the pursuit of personalization and quality. There are also a variety of ceramic functional inks such as metallic texture ink, pearlescent ink and colorful gradient ink on the market. Metallic texture ink gives ceramic tiles a metallic luster and texture, enhancing the sense of modernity and luxury; pearlescent ink creates a glittering effect through pearlescent pigments and presents a pearly luster; colorful gradient ink achieves a smooth transition of multiple colors on a single tile, creating a unique visual layering. These ink types enrich the decorative effects of ceramic products, meet different styles and design requirements, and promote technological innovation and product diversification in the ceramic industry.
[0004] However, these existing ceramic functional inks still have some shortcomings in practical applications. For example, traditional glossy inks may use raw materials containing more harmful substances during preparation, and the frit raw materials used are hard and difficult to disperse, resulting in high production costs, and are also prone to defects such as pinhole bubbles; at the same time, glossy inks are generally oily and easily repel water-based glazes, resulting in glaze defects. Matte inks have problems such as poor texture, easy pinhole bubbles, and difficult processing; metallic inks, pearlescent inks, and colorful gradient inks may also have limitations in certain performance or applications.
[0005] Metamorphic ink is a new type of glossy ink independently developed by the applicant. This ink is a ceramic functional ink, which is different from traditional glossy ink, matte ink, metallic ink, pearlescent ink and colorful gradient ink in chemical composition, physical properties and decorative effect. The characteristic of metamorphic ink is that it can form a crystal structure, which undergoes phase change during the firing process to form crystals with different refractive indices, so that the glaze layer can produce a metallic flash effect under light, presenting a unique texture and color change, which is expected to bring new decorative effects and performance improvements to ceramic products. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a metamorphic ink and a preparation method thereof, and a ceramic rock plate, wherein the metamorphic ink undergoes a phase change during the firing process to form crystals with different refractive indices, thereby producing unique texture and color changes without adversely affecting the quality of the glaze.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a metamorphic ink, wherein the raw material components of the metamorphic ink include metamorphic glaze, inorganic active agent and ink additive, wherein the inorganic active agent is selected from at least one of nano titanium dioxide, nano zinc oxide and nano aluminum oxide;
[0008] The raw material components of the metamorphic glaze include, by weight:
[0009]
[0010] The metamorphic ink of the present invention uses metamorphic glaze of specific components and inorganic active agent as main raw materials, wherein: the raw materials in the metamorphic glaze will undergo complex physical and chemical processes during high-temperature firing to form a stable crystal structure and produce unique texture and color changes; the inorganic active agent is not only conducive to improving the stability and adhesion of the ink, but also can improve the optical properties of the ink and promote the growth of crystals, thereby further enhancing the texture and color changes of the glaze surface. Its mechanism of action is as follows:
[0011] When light passes through materials with different refractive indices, the propagation direction will change. The metamorphic ink of the present invention contains titanium oxide crystals with a refractive index of 2.30 and / or zinc oxide crystals with a refractive index of 2.00, and glass phase materials with a refractive index of 1.47. When light passes through these materials, different degrees of refraction will occur due to their different refractive indices.
[0012] First, the different refraction angles and the influence of crystal arrangement will produce changes in the glaze texture. Due to the different refractive indices of different crystals, the refraction angles of light between them will also be different. This makes the propagation path of light in the glaze layer complex and diverse. When light is refracted at the interface of different crystals, it will bend and scatter. This scattering effect will cause the light originally in a single direction to be dispersed in different directions, thus forming a complex light distribution in the glaze layer. This complex light distribution will cause the surface of the glaze layer to present different light and dark changes and layering, thereby producing a unique texture effect. For example, some areas may appear bright due to the concentration of light, while other areas may appear darker due to the scattering of light, thus forming a texture contrast. At the same time, during the firing process, the growth and arrangement of crystals are random. Crystals with different refractive indices may be arranged together in different ways, further increasing the complexity of the texture. When light passes through these randomly arranged crystals, it will be affected by different crystals, producing richer refraction and scattering effects. This combination of randomly arranged crystals can form a variety of textures, such as spots, stripes, meshes, etc.
[0013] Secondly, wavelength selective refraction and interference and diffraction effects will produce changes in the color of the glaze. Different colors of light have different wavelengths. When light passes through crystals with different refractive indices, light of different wavelengths will be refracted to different degrees. For example, titanium oxide crystals with a higher refractive index may produce a stronger refraction effect on certain wavelengths of light, while glass phases with a lower refractive index may produce a weaker refraction effect on other wavelengths of light. This wavelength selective refraction will cause the propagation path and intensity of light of different colors in the glaze layer to change, so that the glaze layer presents different colors. At the same time, when light propagates between crystals with different refractive indices, interference and diffraction phenomena will also occur. Interference refers to the superposition or cancellation of the peaks and troughs of two or more beams of light when they meet, resulting in light and dark stripes or color stripes. Diffraction refers to the deviation of light from the straight-line propagation direction when encountering obstacles or small holes, forming diffuse light spots or colored halos. These interference and diffraction effects will cause the light in the glaze layer to produce more complex color changes, increasing the artistic effect of the glaze layer.
[0014] Specifically, during high-temperature firing, feldspar and calcium carbonate in metamorphic glazes decompose and react with other components to form new mineral phases, such as calcium feldspar and calcium aluminum silicate, which contribute to the formation of a stable crystal structure. Wollastonite and quartz powder react with other components at high temperatures to form silicate crystals, which rearrange during cooling to form a unique texture. Zinc oxide and aluminum oxide form zinc aluminum spinel at high temperatures, which rearrange during cooling to form a unique luster and color. Hydromica powder and nepheline powder form mica crystals and nepheline crystals at high temperatures, which recrystallize during cooling to form a unique texture.
[0015] At the same time, halloysite can provide good suspension and fluidity, enhance the stability of the glaze slurry; when mixed with other raw materials, it can be evenly dispersed to prevent precipitation. Nepheline can provide high temperature stability and enhance the heat resistance of the glaze layer; it reacts with other ingredients at high temperatures to form a stable crystal structure. Feldspar acts as a flux to lower the melting point of the glaze and promote sintering; it reacts with SiO in the system. 2 、Al 2 O 3 Reacts with other ingredients to form a glass phase, which enhances the gloss and hardness of the glaze layer. Hydromica can provide good gloss and transparency and enhance the decorative effect of the glaze layer; reacts with other ingredients at high temperature to form a uniform glaze layer. Wollastonite can provide high-temperature strength and wear resistance, enhance the mechanical properties of the glaze layer, and react with ingredients such as CaO and MgO to form a stable crystal structure. Quartz powder can enhance the hardness and wear resistance of the glaze layer, react with other ingredients to form a glass phase, and enhance the gloss and hardness of the glaze layer. Calcium carbonate acts as a flux to lower the melting point of the glaze and promote sintering; decomposes at high temperatures to release CaO, and reacts with other ingredients to form a stable crystal structure. Zinc oxide can enhance the gloss and transparency of the glaze layer, and reacts with SiO 2 、Al 2 O 3 The same ingredients react to form a uniform glaze layer.
[0016] In some embodiments of the present invention, the preparation step of the metamorphic glaze includes: mixing the raw materials for preparing the metamorphic glaze, wet ball milling, drying and powdering, and calcining at 1000-1050°C for 7-8 hours to obtain a powder with a median particle size of 10-15μm.
[0017] Specifically, the high-temperature calcination process of metamorphic glaze can not only remove organic matter and other impurities in the raw materials, ensuring the purity and quality of the final product; but also during the calcination process, the chemical components in the raw materials will react to form new mineral phases and crystal structures. At the same time, calcination is also beneficial to improve the hardness, strength and wear resistance of metamorphic glaze, and enhance its application performance in ceramic products. The high temperature environment during the calcination process helps to form a stable crystal structure, ensuring that no adverse changes will occur during the subsequent firing process.
[0018] In some embodiments of the present invention, the ink additives include a solvent, a composite dispersant and a functional additive.
[0019] In some embodiments of the present invention, the functional additive is selected from at least one of potassium phosphate, ferrous sulfate, potassium oxalate, magnesium nitrate, calcium stearate, zinc stearate, butylated hydroxyanisole, and parabens.
[0020] Specifically, potassium phosphate, as a flux, can reduce the melting point of the ink and promote sintering; react with other components to form a stable crystal structure, and enhance the adhesion and gloss of the ink. Ferrous sulfate, as an oxidant, can improve the wear resistance and oxidation resistance of the ink; react with other components to form a stable crystal structure and enhance the physical properties of the ink. Potassium oxalate, as a complexing agent, can improve the stability and fluidity of the ink; react with other components to form a stable complex to prevent particle precipitation. Magnesium nitrate, as a flux, can reduce the melting point of the ink and promote sintering; react with other components to form a stable crystal structure, and enhance the adhesion and gloss of the ink. Calcium stearate and zinc stearate, as lubricants, can improve the fluidity and stability of the ink; react with other components to form a stable complex to prevent particle precipitation. Butylated hydroxyanisole and parabens, as antioxidants, can improve the oxidation resistance and stability of the ink; react with other components to form a stable complex to prevent particle precipitation.
[0021] In some embodiments of the present invention, the solvent is selected from at least one of isopropanol, n-butanol, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, acetone, methyl ethyl ketone, N-methylpyrrolidone, dimethylformamide, methyl formate, and butyl acetate.
[0022] Specifically, the main functions of the solvent in the metamorphic ink are dissolution and dispersion, viscosity adjustment and drying speed control. The above solvent can dissolve and disperse the metamorphic glaze and inorganic active agent, so that they are evenly distributed in the ink, ensuring the stability and uniformity of inkjet printing. At the same time, the viscosity of the ink can be adjusted to meet the requirements of the inkjet printing equipment, ensuring that the ink can pass through the nozzle smoothly to form a uniform pattern and metamorphic ink layer. The evaporation rate of the solvent can control the drying speed of the ink, preventing the ink from drying too quickly or too slowly during the inkjet printing process, affecting the printing effect.
[0023] In some embodiments of the present invention, the composite dispersant includes a cationic wetting dispersant, a nonionic wetting dispersant, an amphoteric wetting dispersant, an electrically neutral wetting dispersant and a polymeric super dispersant.
[0024] Specifically, the dispersants work synergistically to achieve optimal effects in metamorphic inks, ensuring that the inks maintain stability and uniformity during inkjet printing and firing.
[0025] Among them: cationic wetting and dispersing agents can bind to the negatively charged surface of particles to prevent particle aggregation and ensure the uniformity and stability of the ink. Nonionic wetting and dispersing agents can remain stable at different pH values and are suitable for various ink systems. They bind to the particle surface through the van der Waals force between molecules to form a stable dispersion system. Amphoteric wetting and dispersing agents can adjust the dispersion effect at different pH values and bind to the particle surface through their zwitterionic structure, which has strong adaptability. Neutral wetting and dispersing agents can remain stable in different charge environments to prevent particle aggregation. Polymeric superdispersants have a high molecular weight and can effectively coat particles. They bind to the particle surface through their polymer chains to form a stable dispersion system to prevent particle precipitation.
[0026] In some embodiments of the present invention, in the composite dispersant, the mass ratio of the cationic wetting dispersant, the nonionic wetting dispersant, the amphoteric wetting dispersant, the electrically neutral wetting dispersant and the polymeric super dispersant is: (15-25): (30-40): (10-20): (20-30): (3-8).
[0027] In some embodiments of the present invention, the cationic wetting and dispersing agent is selected from at least one of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecylpyridinium chloride, and heptyldimethylbenzylammonium chloride.
[0028] In some embodiments of the present invention, the nonionic wetting and dispersing agent is selected from at least one of polyethylene glycol, ethylene glycol monobutyl ether, glycerol, and sorbitol.
[0029] In some embodiments of the present invention, the amphoteric wetting and dispersing agent is selected from at least one of amphoteric polyacrylate and amphoteric polymethacrylate.
[0030] In some embodiments of the present invention, the electrically neutral wetting and dispersing agent is selected from at least one of sodium lauroyl glutamate and lauryl betaine.
[0031] In some embodiments of the present invention, the polymer type hyperdispersant is a polycaprolactone polyol-polyethyleneimine block copolymer type dispersant, which can be specifically selected from at least one of Hypermer KD1, Solsperse 17000, Solsperse 24000, Disperbyk 161, and Disperbyk 163.
[0032] In some embodiments of the present invention, the raw material components of the metamorphic ink include, by weight:
[0033]
[0034] A second aspect of the present invention provides a method for preparing the above-mentioned metamorphic ink, characterized in that it comprises the following steps:
[0035] The raw materials for preparing the metamorphic ink are mixed, ground, and filtered to obtain the metamorphic ink.
[0036] In some embodiments of the present invention, the fineness of the ink after grinding is a median particle size of 100-200 nm.
[0037] In some embodiments of the present invention, the filtration is performed using a multi-stage 1 μm filter element.
[0038] The third aspect of the present invention provides a ceramic rock slab, which comprises a body, a glaze layer, a pattern decoration layer and a metamorphic ink layer from bottom to top, and the metamorphic ink layer is formed by firing the above-mentioned metamorphic ink.
[0039] In some embodiments of the present invention, the upper surface of the metamorphic ink layer further includes a protective glaze layer. The protective glaze is mainly used to protect the underglaze decorative layer from damage by the external environment; it is also beneficial to improve the wear resistance, chemical corrosion resistance and glossiness of the product, and can be applied according to actual production needs.
[0040] In some embodiments of the present invention, the maximum firing temperature is 1200-1220°C.
[0041] In some embodiments of the present invention, the firing cycle is 40-60 minutes.
[0042] A fourth aspect of the present invention provides a method for preparing the above-mentioned ceramic rock plate, comprising the following steps:
[0043] A glaze, an inkjet-printed pattern and a metamorphic ink are sequentially applied on the surface of the blank to form a glaze layer, a pattern decoration layer and a metamorphic ink layer in sequence, and the ceramic rock slab is obtained after drying and firing.
[0044] In some embodiments of the present invention, the chemical composition of the blank includes, by weight percentage: SiO 2 65.21-68.63%, Al 2 O 3 18.63-22.05%,Fe 2 O 3 0.08-0.25%, TiO 2 0.05-0.09%, CaO0.3-0.6%, MgO1.93-2.35%, K 2 O 3.23-3.88%, Na 2 O 2.65-3.17%, loss on ignition 4.5-5.0%.
[0045] In some embodiments of the present invention, the raw material components of the blank include, by mass: 12-16 parts of albite, 24-27 parts of potassium feldspar, 26-30 parts of ball clay, 8-12 parts of bentonite, 3-6 parts of high-temperature sand, 11-15 parts of medium-temperature sand, and 4-6 parts of calcined talc.
[0046] In some embodiments of the present invention, the chemical composition of the glaze includes, by weight percentage: SiO 2 61-65%, Al 2 O 3 19-23%, Fe 2 O 3 0.05-0.1%, TiO 2 0.05-0.1%, CaO 0.1-0.5%, MgO 0.1-0.5%, K 2 O 3-4%, Na 2 O 3.1-3.8%, ZrO 2 3.2-9.6%, loss on ignition 1.5-2%.
[0047] In some embodiments of the present invention, the raw material components of the glaze include, by mass: 18-22 parts of water-ground sodium stone powder, 18-22 parts of potassium-sodium water-abrasive, 8-10 parts of ball clay, 9-11 parts of quartz powder, 11-13 parts of nepheline powder, 7-9 parts of calcined kaolin, 5.5-6.5 parts of aluminum oxide, 6-8 parts of zirconium silicate, 1.5-2.5 parts of zinc oxide, and 5-7 parts of wollastonite.
[0048] The present invention has no special requirements for the body and the glaze, and conventional ceramic rock slab bodies and glazes can be used.
[0049] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0050] (1) The metamorphic ink of the present invention uses metamorphic glaze of specific components and inorganic active agents (at least one of nano-titanium dioxide, nano-zinc oxide, and nano-aluminum oxide) as main raw material components. The raw materials in the metamorphic glaze undergo chemical reactions and physical changes during high-temperature firing to form a stable crystal structure. The inorganic active agent not only improves the stability, adhesion and optical properties of the ink, but also further promotes the growth of crystals. The combined effect of the two makes the glaze surface produce unique texture and color changes.
[0051] (2) Compared with traditional glossy ink, the metamorphic ink of the present invention not only reduces the use of harmful substances and the occurrence of glaze defects, but also has high gloss and transparency, enhancing the visual effect of the product. The gloss can reach 85-90°, the glaze surface is uniform and delicate, without obvious defects, and has high adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a physical picture of the ceramic rock plate prepared in Example 1;
[0053] Figure 2 This is a physical picture of the ceramic rock plate prepared in Example 2;
[0054] Figure 3 This is a physical picture of the ceramic rock slab prepared in Comparative Example 4. DETAILED DESCRIPTION
[0055] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0056] Example 1
[0057] A metamorphic ink, whose raw material components include, by weight: 40 parts of metamorphic glaze, 2 parts of nano titanium dioxide, 20 parts of isopropyl alcohol, 20 parts of n-butanol, 0.1 part of potassium phosphate, 0.1 part of ferrous sulfate, 0.1 part of potassium oxalate, 0.1 part of magnesium nitrate, 0.1 part of calcium stearate, 0.1 part of zinc stearate, 0.1 part of butylated hydroxyanisole, 0.1 part of p-hydroxybenzoate, 1 part of dodecyltrimethylammonium chloride, 1.75 parts of polyethylene glycol, 0.525 parts of glycerol, 0.225 parts of amphoteric polyacrylate, 0.625 parts of sodium lauroyl glutamate, and 0.25 parts of Hypermer KD1.
[0058] Among them: the raw material components of the metamorphic glaze include, by weight: 5 parts of halloysite, 20 parts of nepheline, 10 parts of feldspar, 3 parts of hydromica, 5 parts of wollastonite, 15 parts of quartz powder, 10 parts of calcium carbonate, and 2 parts of zinc oxide.
[0059] The preparation steps of the metamorphic glaze are as follows: mix the raw materials for preparing the metamorphic glaze, add 0.5 parts of sodium hexametaphosphate and 0.25 parts of sodium dodecyl sulfate, add water for wet ball milling (the mass ratio of raw materials to water is 1:0.5), dry and powder, and calcine at 1000°C for 7 hours to obtain a powder with a median particle size of 10-15μm.
[0060] A method for preparing a metamorphic ink comprises the following steps:
[0061] The raw materials for preparing the metamorphic ink are mixed and ground to a median particle size of 200 nm, and then the semi-finished ink is filtered using a multi-stage 1 μm filter element to obtain the metamorphic ink.
[0062] A method for preparing a ceramic rock plate comprises the following steps:
[0063] The surface of the blank is coated with glaze, inkjet printing pattern and metamorphic ink in sequence (two sets of nozzles are used for printing, and the ink output of each nozzle is controlled to be 18g / m 2 ), forming a glaze layer, a pattern decoration layer and a metamorphic ink layer in sequence, which are dried and fired (the firing temperature is 1200°C and the firing cycle is 40min) to obtain a ceramic rock plate.
[0064] Among them, the raw material components of the green body include, by weight: 12 parts of albite, 24 parts of potassium feldspar, 26 parts of ball clay, 8 parts of bentonite, 3 parts of high-temperature sand, 11 parts of medium-temperature sand, and 4 parts of burned talc.
[0065] The raw material components of the glaze include, by weight: 18 parts of water-polished sodium stone, 18 parts of potassium-sodium water-polished material, 8 parts of ball clay, 9 parts of quartz, 11 parts of nepheline, 7 parts of calcined kaolin, 5.5 parts of aluminum oxide, 6 parts of zirconium silicate, 1.5 parts of zinc oxide, and 5 parts of wollastonite.
[0066] Example 2
[0067] A metamorphic ink, whose raw material components, measured by weight, include: 60 parts of metamorphic glaze, 5 parts of nano-alumina, 20 parts of ethylene glycol monomethyl ether, 20 parts of ethylene glycol dimethyl ether, 1.0 part of potassium phosphate, 0.5 part of ferrous sulfate, 0.5 part of potassium oxalate, 0.5 part of magnesium nitrate, 0.5 part of calcium stearate, 0.5 part of zinc stearate, 0.5 part of butylated hydroxyanisole, 0.5 part of p-hydroxybenzoate, 2 parts of cetyltrimethylammonium bromide, 7 parts of ethylene glycol monobutyl ether, 1.75 parts of glycerol, 0.75 parts of amphoteric polymethacrylate, 1.25 parts of lauryl betaine, and 0.5 part of Solsperse 17000.
[0068] Among them: the raw material components of the metamorphic glaze include, by weight: 15 parts of halloysite, 30 parts of nepheline, 25 parts of feldspar, 8 parts of hydromica, 15 parts of wollastonite, 30 parts of quartz, 20 parts of calcium carbonate, and 7 parts of zinc oxide.
[0069] The preparation steps of the metamorphic glaze are as follows: mix the raw materials for preparing the metamorphic glaze, add 0.5 parts of sodium hexametaphosphate and 0.25 parts of sodium dodecyl sulfate, add water for wet ball milling (the mass ratio of raw materials to water is 1:0.5), dry and powder, and calcine at 1050°C for 8 hours to obtain a powder with a median particle size of 10-15μm.
[0070] A method for preparing a metamorphic ink comprises the following steps:
[0071] The raw materials for preparing the metamorphic ink are mixed and ground to a median particle size of 300 nm. The semi-finished ink is then filtered using a multi-stage 1 μm filter element to obtain the metamorphic ink.
[0072] A method for preparing a ceramic rock plate comprises the following steps:
[0073] The surface of the blank is coated with glaze, inkjet printing pattern and metamorphic ink in sequence (two sets of nozzles are used for printing, and the ink output of each nozzle is controlled to be 25g / m 2 ), forming a glaze layer, a pattern decoration layer, and a metamorphic ink layer in sequence, which are dried and fired (the firing temperature is 1220°C and the firing cycle is 60min) to obtain a ceramic rock plate.
[0074] Among them, the raw material components of the green body include, by weight: 16 parts of albite, 27 parts of potassium feldspar, 30 parts of ball clay, 12 parts of bentonite, 6 parts of high-temperature sand, 15 parts of medium-temperature sand, and 6 parts of burned talc.
[0075] The raw material components of the glaze include, by weight: 22 parts of water-polished sodium stone, 22 parts of potassium-sodium water-polished material, 10 parts of ball clay, 11 parts of quartz, 13 parts of nepheline, 9 parts of calcined kaolin, 6.5 parts of aluminum oxide, 8 parts of zirconium silicate, 2.5 parts of zinc oxide, and 7 parts of wollastonite.
[0076] Example 3
[0077] A metamorphic ink, whose raw material components include, by weight: 50 parts of metamorphic glaze, 3 parts of nano zinc oxide, 25 parts of isopropyl alcohol, 25 parts of n-butanol, 0.1 part of potassium phosphate, 0.1 part of ferrous sulfate, 0.1 part of potassium oxalate, 0.1 part of magnesium nitrate, 0.1 part of calcium stearate, 0.1 part of zinc stearate, 0.1 part of butylated hydroxyanisole, 0.1 part of p-hydroxybenzoate, 1 part of dodecyltrimethylammonium chloride, 1.75 parts of polyethylene glycol, 0.525 parts of glycerol, 0.225 parts of amphoteric polyacrylate, 0.625 parts of sodium lauroyl glutamate, and 0.25 parts of Hypermer KD1.
[0078] Among them: the raw material components of the metamorphic glaze include, by weight: 10 parts of halloysite, 25 parts of nepheline, 20 parts of feldspar, 5 parts of hydromica, 10 parts of wollastonite, 20 parts of quartz powder, 15 parts of calcium carbonate, and 5 parts of zinc oxide.
[0079] The preparation steps of the metamorphic glaze are as follows: mix the raw materials for preparing the metamorphic glaze, add 0.5 parts of sodium hexametaphosphate and 0.25 parts of sodium dodecyl sulfate, add water for wet ball milling (the mass ratio of raw materials to water is 1:0.5), dry and powder, and calcine at 1000°C for 7 hours to obtain a powder with a median particle size of 10-15μm.
[0080] A method for preparing a metamorphic ink comprises the following steps:
[0081] The raw materials for preparing the metamorphic ink are mixed and ground to a median particle size of 250 nm. The semi-finished ink is then filtered using a multi-stage 1 μm filter element to obtain the metamorphic ink.
[0082] A method for preparing a ceramic rock plate comprises the following steps:
[0083] The surface of the blank is coated with glaze, inkjet printing pattern and metamorphic ink in sequence (two sets of nozzles are used for printing, and the ink output of each nozzle is controlled to be 20g / m 2 ), forming a glaze layer, a pattern decoration layer, and a metamorphic ink layer in sequence, which are dried and fired (the firing temperature is 1200°C and the firing cycle is 50min) to obtain a ceramic rock plate.
[0084] Among them, the raw material components of the green body include, by weight: 12 parts of albite, 24 parts of potassium feldspar, 26 parts of ball clay, 8 parts of bentonite, 3 parts of high-temperature sand, 11 parts of medium-temperature sand, and 4 parts of burned talc.
[0085] The raw material components of the glaze include, by weight: 18 parts of water-polished sodium stone, 18 parts of potassium-sodium water-polished material, 8 parts of ball clay, 9 parts of quartz, 11 parts of nepheline, 7 parts of calcined kaolin, 5.5 parts of aluminum oxide, 6 parts of zirconium silicate, 1.5 parts of zinc oxide, and 5 parts of wollastonite.
[0086] Comparative Example 1
[0087] The only difference from Example 1 is that the metamorphic ink of Comparative Example 1 does not contain nano titanium dioxide.
[0088] Comparative Example 2
[0089] The only difference from Example 1 is that the nano-silicon dioxide in Example 1 is replaced by the nano-titanium dioxide in the metamorphic ink of Comparative Example 2.
[0090] Comparative Example 3
[0091] The only difference from Example 1 is that in Comparative Example 3, the metamorphic ink in Example 1 is replaced with a traditional glossy ink. The raw material components of the glossy ink include, by weight: 40 parts of glaze, 40 parts of solvent, 5 parts of polyester dispersant, 0.25 parts of leveling agent BYK-352, 0.25 parts of thickener PVP-K-15, 0.25 parts of preservative Clariant Nipaguard BPX and 0.25 parts of defoaming agent BYK-066N.
[0092] Among them: the raw material components of the glaze include, by weight: 10 parts of kaolin, 25 parts of potassium feldspar, 15 parts of sodium feldspar, 5 parts of talc, 10 parts of wollastonite, 20 parts of quartz powder, 10 parts of limestone, and 5 parts of zinc oxide.
[0093] The raw material components of the solvent include, by weight: 50 parts of water, 25 parts of propylene glycol ethyl ether, 15 parts of ethanol, and 10 parts of ethyl acetate.
[0094] Comparative Example 4
[0095] The only difference from Example 1 is that the metamorphic glaze of Comparative Example 4 does not include a calcination step during preparation, specifically: Mix the raw materials for preparing the metamorphic glaze, add 0.5 parts of sodium hexametaphosphate and 0.25 parts of sodium dodecyl sulfate, add water for wet ball milling (the mass ratio of raw materials to water is 1:0.5), and dry and pulverize to obtain.
[0096] Performance Testing
[0097] The relevant properties of the metamorphic ink and ceramic rock plate samples prepared in the above Examples 1-3 and Comparative Examples 1-4 were tested, and the quality of their glaze surfaces was observed. Among them: the glossiness was tested using a gloss meter in accordance with the "Standard Test Method for Specular Gloss" - ASTM D523, the adhesion of the metamorphic ink was tested in accordance with the standard "Adhesion Test Standard" - ASTM D3359, and the stability of the metamorphic ink was tested in accordance with the standard "Paints and Varnishes - Comparison of Contrast (Hiding Power) of Paints of the Same Type and Color" ISO 2814-2007. The test results are shown in Table 1.
[0098] Table 1: Performance comparison of ceramic rock panels of Examples 1-3 and Comparative Examples 1-4
[0099]
[0100] It can be seen from Table 1 that the ceramic rock plates of Examples 1-3 all have high gloss, good ink stability and adhesion, and the glaze surface is uniform and delicate, without obvious defects, and has unique texture and color changes (see Figure 1-2 ).
[0101] Compared with Example 1, Comparative Examples 1-4 have a significantly reduced glossiness of the glaze of the ceramic rock plate, and the ink stability and adhesion also decrease, and the glaze surface not only cannot obtain unique texture and color changes, but also has certain defects. Especially in Comparative Example 4, as shown in Figure 3 As shown, the glaze has low gloss, uneven glaze and serious color difference. Moreover, due to the weak adhesion of ink on the surface of ceramic rock plate, the glaze is mottled and there is serious glaze deficiency, which greatly affects the product quality and visual effect.
[0102] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A metamorphic ink, characterized in that: The raw material components of the metamorphic ink include metamorphic glaze, inorganic active agent and ink additive, and the inorganic active agent is selected from at least one of nano titanium dioxide, nano zinc oxide and nano aluminum oxide; The raw material components of the metamorphic glaze include, by weight:
2. The metamorphic ink according to claim 1, characterized in that: The preparation steps of the metamorphic glaze include: mixing the raw materials for preparing the metamorphic glaze, wet ball milling, drying and powdering, and calcining at 1000-1050° C. for 7-8 hours to obtain a powder with a median particle size of 10-15 μm.
3. The metamorphic ink according to claim 1, characterized in that: The ink additives include solvents, composite dispersants and functional additives.
4. The metamorphic ink according to claim 3, characterized in that: The functional additive is selected from at least one of potassium phosphate, ferrous sulfate, potassium oxalate, magnesium nitrate, calcium stearate, zinc stearate, butylated hydroxyanisole, and parabens.
5. The metamorphic ink according to claim 3, characterized in that: The solvent is selected from at least one of isopropanol, n-butanol, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, acetone, methyl ethyl ketone, N-methylpyrrolidone, dimethylformamide, methyl formate and butyl acetate.
6. The metamorphic ink according to claim 3, characterized in that: The composite dispersant includes a cationic wetting dispersant, a nonionic wetting dispersant, an amphoteric wetting dispersant, an electrically neutral wetting dispersant and a polymer dispersant.
7. The metamorphic ink according to claim 3, characterized in that: The raw material components of the metamorphic ink include, by weight:
8. A method for preparing a metamorphic ink according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials for preparing the metamorphic ink are mixed, ground, and filtered to obtain the metamorphic ink.
9. A ceramic rock plate, characterized in that: The ceramic rock slab comprises a body, a glaze layer, a pattern decoration layer and a metamorphic ink layer from bottom to top, and the metamorphic ink layer is formed by firing the metamorphic ink described in any one of claims 1-7.
10. The ceramic rock plate according to claim 9, characterized in that: The maximum firing temperature is 1200-1220° C.; and / or the firing period is 40-60 min.
Citation Information
Cited By
Archaistic ceramic tile
CN121342557A